The skin and its diseases : a subject collection from the Cold Spring Harbor perspectives in medicine - Watt, Fiona M.; Oro, Anthony (Cold Spring Harbor Laboratory Press, 2014)
"The skin is a continually renewing organ that acts as a protective barrier isolating us from the external environment. This book examines the cells that make up the skin and their functions, as well as diseases such as psoriasis that affect the skin and new molecular strategies for treating these"--